Xu Guangqi’s Thought On Supplementing Confucianism With Christianity - Anna Seo (Bina Nusantara University, 2012)
Xu Guangqi is one of the most influential Chinese scholars who accepted Christian faith during the late Ming dynasty. His idea of “supplementing Confucianism and replacing Buddhism by Christianity” had great impact on the development of Christianity in China. His idea, however, has often been accused of syncretism, and genuineness of his Christian faith has been put into question. Some argue that his theology lacks Christology. Others suggest that his ultimate goal was to achieve the Confucian political ideals through adopting some of the Christian moral teachings. Through the analysis of Xu Guangqi’ works and life, we find that he accepted all the essential Christian doctrines and Christology is the core of his understanding of “Tianzhu”. His view on Confucianism itself istransformed through Christian perspective. In his new understanding, the ultimate goal of Confucianism is to serve and to worship “Tianzhu”，same as Christianity. The ultimate problem of life is to save one’s soul.Xu Guangqi considered his scientific works as a way to propagate Christian faith,since science was seen as an integral part of Christian thought and practice. His idea of “supplementing Confucianism by Christianity” integrated Confucianism into the overarching framework of Christian thought.